Factors of Indonesia Economic Growth (2017-2022) - Triansyah, Fadli Agus; Gunawan, Ashari; Ramadhaniyati, Resti (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2023)
Economic growth is measured by changes in a country’s Gross Domestic Product (GDP), which can be unraveled into the population and economic elements. This research is conducted to find trends and identify publications on economic growth in Indonesia in the 2017–2022 period. The data collection techniques by downloading files from the Scopus database to see publication trends with the highest number of documents, ranking classifications of institutions or universities, journals, and documents, and using shared keywords. The method used is bibliometric analysis. A total of 168 documents collected from the Publish or Perish (PoP) application using the Scopus database were combined into one file in RIS format and entered into the VOSviewer application to obtain network visualization and overlay visualization. The study results show that the trend of publications related to economic growth in Indonesia for the last six years has decreased yearly. The highest number of documents is in the “International Journal of Energy Economics and Policy,” with 20 documents, followed by the Haseeb (2019) article, totaling 120 citations. Based on the keywords that have been visualized, several keywords are factors of economic growth in Indonesia from 2017 to 2022, namely Energy Consumption, Investment, CO2 Emissions, Education, GDP, Inflation, FDI, Exchange Rate, Export, Government Expenditure, Income Inequality, Inequality, Human Capital, Human Development Index, and Sustainable Development.